Design and Control of Grid Connected Photovoltaic System - Singh, Nagendra (My University, 2021)
Renewable Energy Systems (RESs) are poised to address the concerns arising due to excessive usage of depleting fossil fuels and global warming. Among various renewable resources namely wind, solar, fuel cells, and hydro; solar energy is being harnessed prominently because it is freely available, does not involve moving parts, and can be placed near the load centers. However, the Photovoltaic (PV) source is characterized by intermittent output and wide operating range and therefore requires power converters or Power Conditioning Unit (PCU) for grid interconnection. From the viewpoint of easy maintenance and cost-effectiveness, the grid-tied structure can be advantageous for the PV system as they do not use batteries for energy storage. Different configurations of PCUs have been investigated for various RESs. The two-stage structure is generally used with PV systems having low and fluctuating output voltage. Such structure is usually operated utilizing a DC-DC converter to regulate the PV output voltage and maximize the output power, whereas the inversion process is achieved through an inverter. Traditionally, two-level Voltage Source Inverter (VSI) and Current Source Inverter (CSI) are widely used for grid integration. The VSI is a buck converter and requires an additional DC-DC boost converter to boost its DC-link voltage; while CSI is a boost converter and requires a DC-DC buck converter for buck operations. The impedance source inverters, which characterize single-stage power converters, provide voltage boost ability within the inversion stage. This group of PCUs is poised to be a viable option in comparison to the two-stage arrangement for low and fluctuating voltage sources. The Z-Source Inverter (ZSI) is a single-stage topology proposed to overcome the shortcomings of VSI and CSI. However, ZSI provides a boost in single-stage but is not a preferable candidate for PV as it takes discontinuous current from the source. The Quasi-Z-Source (QZS) inverter, a modified form of ZSI, is suitable for PV systems because it draws continuous current from the source and has a low component rating. The QZS inverter has attracted considerable attention in PV power generation applications because of single-stage power conversion, no dead time between switches of same bridge leg, the ability to handle wide DC voltage, and drawing continuous current. During the boost mode, the DC-link voltage of the QZS inverter pulsates between zero and maximum value. A strategy is proposed to indirectly control the Peak DC-Link Voltage (PDV) of the QZS inverter fed grid-tied PV system by sensing the voltages of QZS network capacitors. Consequently, a two-stage like control structure is discussed where the Shoot-Through (ST) duty ratio is used to regulate the DC-link voltage and AC-current is controlled to control active and reactive power injection into the grid. For the purpose, the AC- and DC-sides are modeled separately and the crossover frequency of the AC-side control loop is kept high to avoid intruding with the DC-side. A Third-Order-Integral-Lead (TOIL) controller is realized to regulate PDV and minimize the Non-Minimum Phase (NMP) characteristic effect of ST duty-ratio to PDV transfer function. A damped-Second-Order-Generalized-Integrator (SOGI) offering high power frequency gain is used to control the AC-side current and attain Zero Steady-State Error (ZSSE). The performance of the proposed TOIL and damped-SOGI controllers is compared with other designed linear and Sliding Mode Controller (SMC). Grid integration of PV systems although leads to efficient utilization of generated power, the efficiency of the grid integration system depends essentially on the performance of the power conditioner and the capability of the adopted control strategies in achieving high performance. The topologies employed in interconnecting the PV system to the grid can be classified into single-stage or two-stage and two-level or Multi-Level Inverters (MLIs). The MLIs are characterized by high power quality at the AC-side, reducing the filter size significantly, operating at higher voltage levels, and reducing switching losses. The Three-Phase (3-) Neutral-Point-Clamped (NPC)-QZS inverter is set to become a potential candidate for renewable energy applications because it yields a continuous input current and voltage boost. A dynamic model has been developed to design the control strategy accurately of the 3- NPC-QZS inverter. The proposed method includes the control of grid-tied current and the PDV. The control of grid-tied current is achieved through a damped-SOGI. The PDV is estimated indirectly from the voltages of QZS network capacitors and is regulated by an Integral-Double-Lead (IDL) controller. Two modified modulation techniques based on Phase-Opposite Disposition (POD) and In-Phase Disposition (IPD) are proposed to yield ST by injecting 3rd harmonics for Maximum Constant Boost Control (MCBC). A comparison is drawn between the performance of the proposed controller and SMC on the DC-side. Transformer less grid-tied inverters have been widely accepted in RESs applications owing to higher efficiency, relatively inexpensive, and compact design. The fundamental buck characteristic of the output voltage is the bottleneck. It requires a DC-DC boost converter, which causes an expensive performance for single-stage energy conversion. A novel single-stage transformer less Switched Capacitor (SC)-based inverter topology is presented to boost the input voltage value and limit the start-up and charging current problem through the QZS network between PV and SC inverter. Likewise, the insertion of the QZS network provides additional control freedom in terms of the ST duty ratio to regulate the DC-link voltage. Due to this hybridization, the size of inductors in the QZS network is reduced. Furthermore, to inject the AC-current to the grid, a damped-SOGI controller is utilized, which can control both the active and reactive power. Large-scale solar PV systems encounter unpredictable Partial Shaded Condition (PSC). The PSC, causing multiple peaks in the Power–Voltage (P–V) characteristics, potentially downgrades the performance of the PV system. However, it is recommended that the PV system should be operated at Global Maximum Power Point (GMPP) to extract maximum power and efficient utilization. The Flying Squirrel Search Optimization (FSSO), a search and optimization algorithm, has been implemented in a real-time manner to track the GMPP for different PSCs. For an effective adoption with a much-reduced convergence time, the original FSSO is modified to update the squirrel position without the presence of the predator. An investigation of the proposed scheme is carried out employing a QZS converter. The proposed method yields higher tracking efficiency, non-oscillatory steady-state response, and lower transients. The performance of the developed FSSO algorithm under different shading conditions is compared with Perturb and Observe (P&O), Particle Swarm Optimization (PSO), and Grey Wolf Optimization (GWO) based algorithms to track the GMPP.
Keywords: AC-side controller; DC-side controller; Maximum power point tracking algorithm; Neutral-point-clamped; Quasi-Z-source inverter; Switched capacitor